Impact Of Perceived Organizational Support For Employee: A Systematic Review - Hernandias Argo , Annisa Lestari Kadiyono , Marina Sulastiana (Migration Letters, 2024)
Perceived organizational support not only has a significant impact but also contributes positively to a company’s overall performance. When employees are treated well by both the organization and their superiors, it fosters a reciprocal relationship that benefits both parties. Currently, in the realm of the workforce, 84% of Indonesian workers exhibit a tendency to change workplaces, with one of the reasons being the desire for a conducive environment for learning and personal growth. Hence, it becomes imperative for companies to provide effective support to their employees, fostering their development and, in turn, positively influencing the company’s outcomes. Despite the critical role perceived organizational support plays, there is a dea[1]rth of studies examining its impact on employees. This review addresses this gap by utilizing databases such as Scopus, Sage journal, Emerald, and Springer, searching for terms related to perceived organizational support and employee-related terms. The articles considered for this review delve into variables influenced by perceived organizational support and elucidate its impact. In total, 21 papers meeting the inclusion criteria were included in this comprehensive review.